Virtual Ethnography: Digital Activism Against Non-Binary Gender On Social Media Platform X - Kevin Rasyid Sabili Nasution; Fakhrur Rozi (UNIVERSITAS PAKUAN, 2025)
This article analyses digital activism that rejects non-binary gender identities on Social Media Platform X, considering how online activity can reshape social norms and traditional values in Indonesia. This study employs a qualitative methodology with a virtual ethnographic approach to observe and analyse the behaviour and interactions of social media users concerning non-binary gender issues. Data were collected through post analysis and direct observation of user tweets that formed part of ongoing online discussions. The research provides insight into how non-binary narratives are widely rejected. Findings reveal that digital activism opposing non-binary gender identities often relies on narratives rooted in traditional and religious values, reflecting a broader disapproval of non-binary gender recognition. Social media serves as a catalyst for high engagement and further reinforces the polarisation of these views.